On the evolution of low-mass central galaxies in the vicinity of massive structures - Palma, Daniela; Lacerna, Ivan; Artale, Maria Celeste; Montero Dorta, Antonio David; Ruiz, Andrés Nicolás; Cora, Sofía Alejandra; Rodriguez, Facundo; Pallero, Diego; O’Mill, Ana; Choque-Challapa, Nelvy (2024)
Fil: Palma, Daniela. Universidad de Atacama. Instituto de Astronomía y Ciencias Planetarias de Atacama; Chile.